ECONOMIC EFFICIENCY AND INNOVATIVE DEVELOPMENT STRATEGIES IN THE SERVICE SECTOR - Shukurova Nilufar Kaxramanovna (Bright Mind Publishing, 2025)
The service sector is a fundamental pillar of the modern economy, accounting for a significant share of GDP, employment, and value creation in both developed and developing countries. As global economic structures evolve, enhancing the economic efficiency of service industries has become a critical priority for policymakers and business leaders. This study explores the key factors influencing economic efficiency in the service sector, with a focus on innovative development strategies that drive productivity, cost-effectiveness, and service quality improvement. The paper examines the role of digital transformation, automation, and artificial intelligence in optimizing service delivery, streamlining operations, and reducing inefficiencies. Furthermore, the study analyzes policy frameworks, investment strategies, and regulatory measures that contribute to the sustainable and competitive growth of service-based economies. Through a comprehensive review of technological advancements and best practices, this research highlights how innovation-driven strategies can enhance profitability, customer satisfaction, and overall sectoral performance.
Keywords: Service sector, economic efficiency, digital transformation, innovation strategies, automation, artificial intelligence, productivity, cost-effectiveness, service quality, technological advancements, policy frameworks, sustainable growth, competitiveness, data-driven decision-making.